Eco-friendly and scalable strategy to design electrically insulating boron nitride/polymer composites with high through-plane thermal conductivity - Jang, Wooree; Lee, Seoyun; Kim, Nam Ryeol; Koo, Hyeyoung; Yu, Jaesang; Yang, Cheol-Min (Pergamon Press Ltd., 2023)
Hexagonal boron nitride (h-BN)/epoxy composites with high through-plane thermal conductivity were suc-cessfully fabricated using core-shell h-BN/epoxy (e-BN) microspheres which were synthesized using a simple one-pot emulsion polymerization process in an eco-friendly aqueous medium. e-BN microspheres covered with self-assembled h-BN flakes (1 mu m lateral size) on the surface of the epoxy microspheres facilitated the effective alignment and distribution of the flakes in the epoxy matrix. The e-BN/BN/epoxy composites fabricated by mixing the e-BN microspheres with the h-BN flakes (17 mu m lateral size) exhibited far higher through-plane thermal conductivity than the BN/epoxy composites (without e-BN microspheres) with the same h-BN flake content. In particular, the e-BN/BN/epoxy composite with 50 wt% (33 vol%) h-BN flakes exhibited excellent through-plane thermal conductivity of 4.27 W/mK, which was approximately 3.7 times that of the BN/epoxy composite (1.17 W/mK), owing to a more random or isotropic orientation of the h-BN flakes in the e-BN/BN/ epoxy composite. The experimentally measured thermal conductivities were well matched to those obtained from micromechanical estimations using the modified Mori-Tanaka method. We expect that this eco-friendly and scalable fabrication process of e-BN microspheres and e-BN/BN/epoxy composites could provide an innovative strategy for manufacturing electrically insulating polymer composites with high through-plane thermal conductivity.